Ion energy distributions for collisional ion sheaths at an rf-biased plasma electrode - Qin, Xueying victor (My University, 2010)
In plasma etching for materials processing, ions are often accelerated towards the substrate via a sheath electric field generated by a bias voltage applied to the substrate electrode. By applying at tailored bias waveform to the electrode the resulting ion energy distribution can be manipulated to have a single narrow peak at a specified energy. For low neutral pressures, ion motion through the sheath is collisionless, and nearly all the incident ions strike the substrate with the full ion energy dictated by the bias waveform. However, as the plasma conditions are adjusted and the sheath thickness becomes long compared to the ion mean free path, the sheath becomes collisional. As ions undergo charge-transfer collisions while traversing the sheath, they strike the substrate with a lower ion energy than dictated by the bias waveform. As the system becomes more collisional, the peak of the ion energy distribution is suppressed, and the ion flux of lower-energy ions increases. Ion energy distributions at the substrate are measured with a retarding field energy analyzer for many systems of various collisionality, and the aforementioned effects of the collisional sheaths are observed.